2004
DOI: 10.1111/j.1365-2621.2004.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed‐vacuum immersion of chicken meat and skin in acid solutions. Effects on mass transfers, colour and microbial quality

Abstract: Decontaminating chicken skin by immersion in an organic acid solution at low temperature (7°C) led to 3.7, 2.5, 2.4 and 2.0 decimal reductions in total viable counts, Enterobacteriaceae, total coliforms and Escherichia coli, respectively. Lactic acid was a more effective decontaminating agent than citric acid. This decontaminating effect was very closely correlated with solution pH and chicken-skin pH variations. The use of pulsed vacuum immersion (PVI) increased mass transfers (water gain and acidification) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…3b). This result is similar to those reported in the acidification of chicken meat using pulsed vacuum immersion (Deumier, 2004) and in the osmotic dehydration of apple (Mújica-Paz, et al, 2003a) and orange peel (Cháfer, González-Martínez, Ortola, & Chiralt, 2001) with initial vacuum pulse application. This general pattern may be associated with the relatively high porosity of the products or with the vacuum pulse levels.…”
Section: Weight Reduction (Wr)supporting
confidence: 93%
See 3 more Smart Citations
“…3b). This result is similar to those reported in the acidification of chicken meat using pulsed vacuum immersion (Deumier, 2004) and in the osmotic dehydration of apple (Mújica-Paz, et al, 2003a) and orange peel (Cháfer, González-Martínez, Ortola, & Chiralt, 2001) with initial vacuum pulse application. This general pattern may be associated with the relatively high porosity of the products or with the vacuum pulse levels.…”
Section: Weight Reduction (Wr)supporting
confidence: 93%
“…These results indicate that during the traditional pickling process pepper dehydration predominates, while water gain of jalapeño pepper can occur on certain conditions of pickling with initial VP. External solution uptake, and consequently water gain, has also been observed in the osmotic dehydration of apple (Mújica-Paz, et al, 2003a) and papaya (Moreno et al, 2004) with vacuum pulse application, as well as in the brining of meats and impregnation of acid solutions into the follicles of poultry skin Deumier, 2004). The uptake of external solution has been attributed to the pressure changes to which the solid-liquid system is exposed.…”
Section: Water Loss (Wl)mentioning
confidence: 96%
See 2 more Smart Citations
“…The antibacterial effect of lactic acid varies depending on the concentration, temperature and the method of application (Tamblyn and Conner 1997). The effect of lactic acid on meat quality and sensory properties has been studied in different species such as cattle, chicken, buffalo and pig (Jimenez-Villareal et al 2003ab, Kotula and Thelappurath 1994, Pipek et al 2005, Deumier 2004, Surve et al 1991, Van Netten et al1995, Jensen et al 2003. The parameter most studied is color and it has been observed that the modifications that occur depend mainly of the lactic acid concentration, and method applied.…”
Section: Introductionmentioning
confidence: 99%